Overview of ultraviolet‐based methods used in polycyclic aromatic hydrocarbons analysis and measurement. Issue 4 (20th January 2020) - Mansouri, Elham; Yousefi, Vahid; Ebrahimi, Vida; Eyvazi, Shirin; Hejazi, Mohammad Saeid; Mahdavi, Mehri; Mesbahi, Asghar; Tarhriz, Vahideh
Abstract: Polycyclic aromatic hydrocarbons are environmental carcinogens that enter the environment through various routes. Therefore, the detection and remediation of carcinogens is one of the priorities of environmental research projects. Polycyclic aromatic hydrocarbons show very specific ultraviolet absorbance spectra. The majority of polycyclic aromatic hydrocarbons have an absorption in the ultraviolet or visible region; hence, ultraviolet‐visible spectroscopy has an important role in the detection of these compounds. Moreover, ultraviolet‐detectors with high‐performance liquid chromatography is a conventional method for identification, characterization and determining of polycyclic aromatic hydrocarbons in complex environmental samples. In this review, attempts have been made to critically and objectively review the related literature and present the theoretical and practical background of the previous research on reproducible and successful ultraviolet‐based methods especially in high‐performance liquid chromatography‐ultraviolet, high‐performance liquid chromatography ultraviolet‐diode array detector and ultraviolet‐fluorescent detector, were used in scientific studies to measure polycyclic aromatic hydrocarbons concentration. The review provides useful and comprehensive information about valuable methods for future researches on polycyclic aromatic hydrocarbons remediation.